The Influence of Android-Based Isomorphic Physics (Forfis) Application on Analogical Transfer and Self-Diagnosis Skill of Students at SMA Negeri 3 Kupang - Sari, D. K.; Supahar, S.; Ralmugiz, U. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
This research intended to understand the effect of Isomorphic Physics (FORFIS) application to the analogical transfer and self-diagnosis skill of high school students. The use of Android applications in physics learning has given a considerable influence in improving the various abilities of learners. However, no one has measured the influence of the Android application on the analogical transfer and self-diagnosis skill of students, especially in physics subject. This research type was experimental research of pre-test post-test control group design. The subjects involved in this research were 1 physics teacher and 87 students of SMA Negeri 3 Kupang; 28 students in the experimental class I (G1), 35 students in the experimental class II (G2), and 24 students in the experimental class III (G3). The data obtained were analyzed using the ANOVA Mixed Design method in combination with General Linear Model. The results of the analysis show that the FORFIS application could improve 0.912 or 91.2% of the students’ analogical transfer and self-diagnosis skill. Therefore, the FORFIS application employed in physics learning had a great influence on the improvement of analogical transfer and self-diagnosis skill of high school students.